Kumaraswamy Uniform Distribution: Model, Properties, and Applications - Tharu, Ramesh Prasad; Dhungana, Govinda Prasad; Joshi, Ramesh Kumar (Journal of Institute of Science and Technology, 2023)
Three parameters Kumaraswamy Uniform distribution has been derived from the Kumaraswamy family of distribution with uniform distribution, whereis scale parameter, andare the shape parameters. The proposed model is unimodal and negatively skewed, whereas the hazard rate function is bathtub and inverted bathtub shaped. The statistical properties like as, the reliability/survival function, the hazard rate function, the quantile function, the median, and the mode have been derived from the proposed model. The parameters are obtained from the maximum loglikelihood function which is equivalent to the maximum likelihood function. Using real-data analysis, the proposed model is unimodal, and the negatively skewed distribution is well-fitted distribution observed by the P-P plot, estimated CDF with empirical distribution, and KS test value. Finally, the proposed model is compared to various competitive models available in the literature, and the results revealed that the proposed model performs better than other models in terms of finding the least value of AIC, BIC, CIAC, and HQIC. Hence, the proposed model is an alternative model of lifetime data.